Internalization of local Values in Early Children's Education on the Bugis Local Wisdom - Muhammad Akil Musi; Azizah Amal; Herlina Herlina; Sri Wahyuni Asti; Noviani Noviani (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The Bugis community has the value of local wisdom as a genetic heritage that can be instilled in moral values in early childhood. The purpose of the study was to determine the value of local Bugis understanding in educating children's morals. The research was conducted in Bone. The type and approach used in this research is descriptive qualitative phenomenology. Research informants consisted of several parents of 10 selected children. Data analysis used an interactive descriptive analysis model through the stages of data reduction, presentation, verification, and conclusions. The results show there are several manifestations of local wisdom of the Bugis community in educating children's morals; namely the values of siri (shame and self-respect), ade' (customs) or pangadereng (customs and traditions system), sabbara' na mamekko (patience and silence), reso teng mangingi (relentless hard work), pemmali (abstinence or prohibition against taboos), malempu (honest), and appasitinajang (worthiness or appropriateness)